Biochemical Monitoring of Detoxifying Enzyme Levels in Field Population of Mosquitoes: Culex quinquefasciatus Say and Aedes aegypti (L.): Biochemical Monitoring of Detoxifying Enzyme Levels in Field Population of Mosquitoes: Culex quinquefasciatus Say and Aedes aegypti (L.) - Pushpalatha, E. (International Journal of Pharmaceutical & Biological Archive, 2018)
The major cause of resistance mechanism in mosquitoes is the detoxification and degradation of insecticides by overproduction of various metabolic enzymes. Quantitative metabolic enzyme assays of carboxylesterases (Î± and Î²), mixed function oxidases (MFO), and glutathione S-transferases (GST) have been commonly used in the detection of insecticide resistance due to its sensitive nature even at low frequencies. For the present study, larval strains of Culex quinquefasciatus Say and Aedes aegypti (L) were collected from the Cochin Corporation, Kerala, India, and were assayed to organophosphate temephos and carbamate propoxur. The resistance ratio of median lethal time for temephos and propoxur from the field population of C. quinquefasciatus and A. aegypti is higher than the laboratory population. Elevated levels of Î± and Î² esterase enzyme were observed with the ratio of 1.6 and 1.54 for C. quinquefasciatus and 1.51 and 1.47 for A. aegypti. In Culex mosquitoes, 1.71, and in Aedes, 1.64 fold increase in GST enzyme level and 1.38 and 1.3 fold increase for the MFO level determined. The study results revealed the urgent needs of improving the vector control methods by introducing alternative techniques and strategies against mosquitoes.